Syrian refugees' perception of barriers and bridges towards integration into Turkish society - Gursoy, Esim; Ertaşoğlu, Leyla Deniz (Routledge Journals, Taylor & Francis Ltd, 2019)
Population displacements have occurred in tremendous amounts in the last few decades due to the collapse in civil order of the neighbouring countries of Turkey. This situation not only created a need for researchers to deal with the social, psychological and economical aspects of this forced mobility, but also with the acculturation process of the refugees who left their home owing to serious human rights violations. Because they do not occupy a great space in the policy agendas, they are an 'invisible' group. This poses a major problem that there are no specific theories regarding the second language acquisition process of refugees, because they are considered together with all immigrants although their experiences distinguish them from other groups. Thus, feeling the need to be the voice of this unvoiced group with their SLA experiences and witnessing the swiftly changing dynamics in the world, the Middle East in particular, and its impact on the sociocultural context, this paper concentrates on the perceptions of Syrian refugees about the L2 (Turkish) and the target language group (Turkish people).
, Gursoy/0000-0003-3715-4583; ertasoglu, leyla deniz/0000-0003-2689-1529
Keywords: Acculturation; cultural adaptation; immigrant learners; SLA; Syrian refugees